Hydrogeochemical and mineralogical evaluation of groundwater arsenic contamination in Murshidabad district, West Bengal, India - Neal, Andrew W. (Kansas State University, 2010)
More than 75 million people in the Bengal Delta of eastern India and Bangladesh are exposed to drinking water with dangerously high arsenic (As) concentrations; the worst case of environmental poisoning in human history. Despite recognition of dangers posed to chronic exposure to drinking water with elevated As, its biogeochemical cycle is inadequately constrained in groundwater flow systems due to its complex redox chemistry and microbially-mediated transformations. Arsenic concentrations in Bengal Delta sediments are comparable to global averages, but its highly heterogeneous spatial distribution (on scales of meters to kilometers) in sediments and groundwaters is poorly understood. Though many research efforts have targeted understanding this heterogeneity in Bangladesh, less work has been done in eastern India. Murshidabad (23°56.355‘N, 88°16.156‘E), an eastern district in West Bengal, India, where groundwaters are highly As-affected (~4000 μg/l), was chosen as our study area. Research objectives were: (1) characterize sediment cores (mineralogically, geochemically) and groundwaters (hydrochemically, isotopically) in areas with contrasting As concentrations—west (low-As) and east (high-As) of river Bhagirathi, a major distributary of Ganges flowing through the heart of Murshidabad; (2) describe and understand the extent of spatial variability, laterally and vertically, of dissolved As concentrations in shallow (< 60 m) aquifers, comparing sediment core chemistry to water chemistry; (3) identify source(s) of aquifer recharge and (4) role(s) of inorganic carbon within the aquifer to understand the bioavailability and mobilization of As from sediments to groundwaters. Mineralogical differences between high-As (grey) and low-As (orange-brown) sediments, were the presence of greater amounts of micas, Fe- and Mg-rich clays, amphiboles, carbonates, and apatite in high-As sediments; these were virtually absent from low-As sediments. In high-As areas, As was associated with amorphous and poorly-crystalline Fe-oxyhydroxide phases and labile (specifically-sorbed) phases, especially where Fe(II):Fe[subscript]T was high in the sediments. High-As groundwaters had high As(III):As[subscript]T, iron, bicarbonate, phosphate, and ammonium, and low concentrations of chloride and sulfate. Dry season precipitation was probably the main source of aquifer recharge; lighter values of [superscript]13C in dissolved inorganic carbon resulted from oxidation of natural organic matter. This study points to an idea that both microbially-mediated oxidation-reduction and competitive ion-exchange processes occurring in shallow aquifers of Murshidabad drive As mobilization and sequestration by aquifer sediments.
Keywords: Arsenic; Geochemistry; Mobilization; Sequential Extraction; Stable Isotope; West Bengal; Environmental Sciences (0768); Geology (0372); Hydrology (0388)